TEKS DAN KONTEKS KEPEMIMPINAN KAUM TUA DALAM NASKAH-NASKAH TAREKAT SYATTARIYAH DI MINANGKABAU - Pramono, Pramono (Institut Agama Islam Negeri (IAIN) Palu, 2009)
This article discusses the efforts of Â intreprating local Islam manuscripts of Minangkabau, particularly the order ofÂ Syattariyah in Minangkabau. The manuscripts are culturally important since they are related to the daily religious needs of the disciples of the order of Syattariyah in Minangkabau. This is related to the beliefs that to know about the guru, to posses the book, or to listen to the stories about the ulema, the guruÂ of the order of Syattariyah are essential. The ideolgical perspectives is influenced by the surau teaching system based on the doctrines and books of the teachers. By means of social context analyses of the texts, it is found that one way to reflect the disciplesâ respect for the guru(-s) has been done through writing the biography of the respective teachers and understanding their teaching.Â Because the guru is considered holy man, his story cannot be written in Latin texts, otherwise it will be considered blasphemy or harÃ¢m.Kata Kunci: Â Â surau, Kaum Tua, Kaum Muda, manuscrip, Tarekat Syattariyah, Minangkabau, Islam.